2018
DOI: 10.11152/mu-1034
|View full text |Cite
|
Sign up to set email alerts
|

The value of ultrasound diagnosis in the multidisciplinary approach of cutaneous tumours. Case report

Abstract: We report the case of a senior patient, presenting with two cutaneous tumours in which the clinical and dermoscopic examination pointed towards a basal cell carcinoma. Ultrasound revealed highly vascularised tumours and elastography showed increased rigidity. Histological examination of both lesions following complete resection was consistent with squamous cell carcinomas. The distinctive feature of this case consists of the complex non-invasive diagnostic imaging of the tumour morphology, performed in real ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…A study conducted on 56 patients with BCC reported lower ultrasonographic index in comparison with histologic index, but a moderate correlation index was obtained and statistically significant differences were not identified (43). HFUS can be similarly useful in detecting subclinical satellite lesions.…”
Section: High Frequency Ultrasonography Of Melanocytic Naevi and Basal Cell Carcinomamentioning
confidence: 86%
See 2 more Smart Citations
“…A study conducted on 56 patients with BCC reported lower ultrasonographic index in comparison with histologic index, but a moderate correlation index was obtained and statistically significant differences were not identified (43). HFUS can be similarly useful in detecting subclinical satellite lesions.…”
Section: High Frequency Ultrasonography Of Melanocytic Naevi and Basal Cell Carcinomamentioning
confidence: 86%
“…HFUS can be similarly useful in detecting subclinical satellite lesions. In another study with 46 subjects diagnosed with BCC (18 patients); superficial spreading melanoma (8 patients) and nodular melanoma (20 patients), the ultrasonographic depth index was comparable to the histological one, with a very good sensitivity (98-99%) (43). BCC with depth index smaller than 1.5 mm may benefit from photodynamic therapy (35).…”
Section: High Frequency Ultrasonography Of Melanocytic Naevi and Basal Cell Carcinomamentioning
confidence: 92%
See 1 more Smart Citation
“…In hyperkeratotic lesions, the sonographic characterization might be limited by the presence of keratin; hence, removing the external hyperkeratotic component might facilitate more accurate imaging of SCC [1,9,37,38].…”
Section: Us In the Pre-and Postoperative Assessment Of Malignant Tumo...mentioning
confidence: 99%
“…1 The main treatment of BCC is surgical excision; therefore, determination of tumor extent pre-operatively is vital for an optimal excision. 2 In order to evaluate tumor extent accurately, high-frequency sonography, dermoscopy, and magnetic resonance imaging are commonly used. 3 Shear wave ultrasound elastography (SWE) is a novel cost-effective diagnostic ultrasound (US) technique using acoustic radiation impulses to stress tissues and ultrafast US tracking techniques to measure the speed of induced shear waves.…”
Section: Can Shear Wave Ultrasound Elastography Be a Useful Tool For mentioning
confidence: 99%